Knowledge, Attitude, and Perceived Barriers of Newly Graduated Registered Nurses Undergoing Standardized Training in Intensive Care Unit Toward Early Mobilization of Mechanically Ventilated Patients: A Qualitative Study in Shanghai - Jiang, Jinxia; Zhao, Sijia; Han, Peng; Wu, Qian; Shi, Yan; Duan, Xia; Yan, Songjuan (Frontiers in Public Health, 2022)
Aim: To explore the knowledge and attitudes of newly graduated registered nurses, who have undergone standardised training in the intensive care unit, about the early mobilization of mechanically ventilated patients and identify perceived barriers to the application of early mobilization. Background: Early mobilization of mechanically ventilated patients has been gradually gaining attention, and its safety and effectiveness have also been verified. Nurses in intensive care units are the implementers of early mobilization, and the quality of their care is closely related to patient prognosis. However, the knowledge and attitude of newly graduated registered nurses undergoing standardized training, in intensive care units, on the early mobilization of mechanically ventilated patients and the obstacles they face in clinical implementation are still unclear. Methods: This qualitative study utilized the phenomenological method to explore the experiences of 15 newly graduated registered nurses undergoing standardized training in intensive care units in a 3rd hospital in Shanghai, China. Semi-structured face-to-face interviews were conducted in June 2020. The Colaizzi seven-step framework was used for data analysis. Findings: A total of 15 new nurses comprised the final sample after data saturation. Three main themes emerged from the analysis and seven subthemes: perceived importance, low implementation rate, and perceived barriers. Conclusions: Newly graduated registered nurses undergoing standardised training in intensive care units have a high level of awareness of the importance of early mobilization of mechanically ventilated patients and are willing to implement it. However, there is a lack of relevant knowledge and other obstacles that restrict clinical implementation. Early mobilization should be included in the standardised training of new nurses in intensive care units.